The Community Resilience Measurement of Tourism Village in The Special Region of Yogyakarta against The COVID-19 Pandemic - Putri, Shinta Permana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article or articles aims to measure the resilience index of tourist village communities in DIY, especially in independent and developed tourist villages, and find the factors that influence it. The problem is focused on the biggest impact of the COVID-19 pandemic faced by local communities that have a large dependence on tourism activities. This research is quantitative. Data was collected through a questionnaire survey conducted with the community of tourism village entrepreneurs in DIY. This research focuses the sample on independent and developed tourist villages that are more prepared to face the pandemic. A total of 130 samples were taken with a confidence level of 92% based on the Slovin formula. The first research objective was analyzed by adopting the HCRI (Household Climate Resilience Index) calculation and the second objective was analyzed using multiple linear regression analysis. HCRI calculations are analyzed with the help of tables, percentages, and HCRI models which are used to assess community resilience based on respondents' responses to 31 resilience indicators. Resilience weights of 1-5 are given to indicators classified on a Likert scale, namely very high (5), high (4), medium (3), low (2), and very low (1), which means household resilience increases as the calculated value increases. The final results of this calculation are classified into five categories starting from very low resilience to very high resilience. The results of the analysis show that communities in developed and independent tourist villages in DIY have relatively high resilience in facing the COVID-19 pandemic. This resilience is influenced by economic, institutional, and social capital factors. However, tourist villages in DIY still need to be aware of the threat of vulnerability that may still occur during the COVID-19 pandemic in 12 indicators related to the economic condition of the community. These results have implications for the need to increase community resilience in developed/independent tourist villages by considering vulnerability factors in this research. In this case, both the government and tourist village managers are advised to focus more on programs to improve the quality of tourism business actors' resources and also the ability to mitigate economic losses after the COVID-19 pandemic to maintain the stability and sustainability of the economy of tourist village communities.